Aplikasi Edukasi Pengenalan Bahasa Arab Berbasis Augmented Reality Studi Kasus : Madrasah Ardhal-Haq - Ibnu Sani Wijaya; Gilang Ramadhan; Masgo Masgo (Jurnal Teknologi Informasi dan Multimedia, 2024)
The field of education is witnessing rapid developments in information technology, with aug-mented reality (AR) emerging as a promising tool for multi-media learning, including Arabic language recognition. Among the Semitic language families, Arabic has the largest number of speakers. Arabic is the sentence that Arabs use to express their intentions and purposes. The form is in the form of hijaiyah letters that are used by Arabs for oral and written social interaction and communication. Madrasah diniyah takmiliyah ardal-haq is located on the main road of pematang moss, betara sub-district, West Tan-jung Jabung district, Jambi Province as one of the elementary schools, at the Ardhal-haq Madrasah, the way of delivering learning is still using simple methods, using books that do not have pictures. it is known that in general students and female students feel bored with Arabic language teaching offered by educational institutions, because students face challenges in understanding written language, including phonetics and syntax. The author chooses to use the MDLC (Multimedia Development Life Cycle) method to conduct research by creating Augmented Reality-based educational applications for Arabic language teaching. This method can be applied to system development in multimedia applications and its stages can be changed based on the research needs, which is why the author used it for system development. The purpose of this research is to facilitate the mastery of Arabic language by students and support instructors of Ardhal-Haq Madrasah in their classroom teaching. With this research produces an Augmented Reality-based Arabic language introduction educational application.